EXPERIMENTAL RESEARCH ON FAILURE OF COMPOSITE SANDWICH π-JOINT - CHENG LiNan; CHI Jian; QU TianJiao; YU Xin (Jixie qiangdu)
The π-joint is put forward and the configuration is designed to meet the need for capacity of pull-off and lateral bending,considering the influence of temperature condition. The test result demonstrates that filler area is the weakest part of the sandwich π-joints where the damage first appears,and determines the capacity of structure. The capacity of π-joint under pull-off load highly than lateral bending load,and the failure mode of sandwich π-joint is sensitive to elevated temperature too cold temperature dry condition.